A spirally rotating backward flow of light - Victor Kotlyar (Компьютерная оптика, 2018)
Using Richards-Wolf formulas, we show that when a left-hand circularly polarized optical vortex with the topological charge 3 is sharply focused in an aplanatic system, a backward near-axis energy flow is observed in the focal plane. While being zero on the axis, the backward flow is only 2-3 times smaller in magnitude than the incident energy flow coming to the focus. It is also shown that near the optical axis the reverse flow propagates spiraling counter-clockwise about the optical axis. The presence of the near-axis backward flow of energy is also shown by the FDTD-aided numerical simulation of diffraction of a circularly polarized plane wave by a third-order spiral zone plate with the NA ≈ 1. A Rayleigh microparticle captured in the focus vicinity is expected to move in the opposite direction to the beam propagation.